2023
DOI: 10.1007/s13318-023-00822-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of N,N-dimethyltryptamine in Humans

Abstract: Background and Objective N , N -dimethyltryptamine (DMT) is a psychedelic compound under development for the treatment of major depressive disorder (MDD). This study evaluated the preclinical and clinical pharmacokinetics and metabolism of DMT in healthy subjects. Methods The physiochemical properties of DMT were determined using a series of in vitro experiments and its metabolic profile was assessed using monoamine oxidase (MAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Various clinical studies of DMT have been performed, but all were single doses or short series of doses that would not be adequate to assess the risk of VHD (e.g., Good et al, 2023;Riba et al, 2015;Timmermann et al, 2019;Vogt et al, 2023;Strassman, 1994aStrassman, , 1994b. The health status of long-term ritualistic users of ayahuasca has also been assessed (e.g., Barbosa et al, 2012), but with significant limitations.…”
Section: In Vivo Dmt Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Various clinical studies of DMT have been performed, but all were single doses or short series of doses that would not be adequate to assess the risk of VHD (e.g., Good et al, 2023;Riba et al, 2015;Timmermann et al, 2019;Vogt et al, 2023;Strassman, 1994aStrassman, , 1994b. The health status of long-term ritualistic users of ayahuasca has also been assessed (e.g., Barbosa et al, 2012), but with significant limitations.…”
Section: In Vivo Dmt Studiesmentioning
confidence: 99%
“…The PK data following inhaled DMT are very limited (Riba et al, 2015), although the PK of IV administration has been studied fairly extensively in recent years (Good et al, 2023;Timmermann et al, 2019;Vogt et al, 2023). A dose-ranging study showed that a 0.05 mg/kg IV bolus of DMT fumarate resulted in an effect intensity equivalent to a microdose and a plasma C max value of approximately 10 ng/mL (Strassman, 1994a(Strassman, , 1994b.…”
Section: Risk Assessment Of Dmtmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Recently, infusions of DMT over varying lengths of time have been evaluated in the clinic. 11,12 The subjective intensity score used in the aforementioned study 7 is a discrete outcome variable that can only assume integer values within certain boundaries. However, the published model treats the intensity ratings as being continuous which means that predictions of non-integer values can also occur.…”
Section: Introductionmentioning
confidence: 99%